Self Assessment In Tax Law - Putri Pramudya, Arlini Hapsari (Devotion : Journal of Research and Community Service, 2022)
Indonesia has changed the tax collection system several times, starting from the official assessment system, semi-self assessment system, withholding system to the self-assessment system. In the self-assessment, the taxpayer will be given confidence in calculating, calculating the tax payable independently and then depositing and reporting to the registered tax service office. This study aims to determine how the implementation of the self-assessment system to taxpayers. This research method uses normative juridical, namely the study of library materials which include primary legal materials, secondary legal materials and tertiary legal materials, both in the form of documents and statutory regulations. The results of the study show that the self-assessment system applied has not been able to change taxpayers in carrying out tax activities independently and honestly. The law gives trust to taxpayers with a self-assessment system, but is not accompanied by good legal awareness by taxpayers. Supervision and application of sanctions that are not optimal result in high violations committed by taxpayers.